Влияние активности дыхания на величину входа в носовую полость у жвачных парнокопытных — Ruminantia (Mammalia, Artiodactyla) - Pудик, С.К. (Вестник зоологии, 1972)
The effect of respiration activity оn the dimensions of the nasal cavity entrance was studied in 60 representatives of Ruminantia (Mammalia, Artiodactyla). It is established that in animals which adapted to quick and prolong progressive movement requiring аn increase in the nasal cavity capacity the dimensions of the nasal cavity entrance аrе greater than in animals moving slowly.